Oil prices, Gold Prices and Exchange Rate in Algeria: A Non-Linear Analysis Prix du pétrole, prix de l'or et taux de change en Algérie: une analyse non linéaire - Ayad, Hicham (Finance and Business Economies Review, 2019)
This analytical review explores the nonlinear links between crude oil prices, gold prices and Algeria Dinar real effective exchange rate for the period January 1990 to December 2016, we use in this paper a Markov Switching Auto-Regressive model (MSVAR) developed by Hamilton (1989), the empirical results show that there are two significant regimes, and the transitions between the two regimes followed the discounts of the Algerian Dinar value by the Central Bank (1991 and 1994), the results show also that oil prices affect the exchange rate by the limited manner especially in the first regime.